2020
DOI: 10.1055/s-0040-1713058
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nano Zinc Oxide Particles on Color Stability of MDX4-4210 Silicone Prostheses

Abstract: Objective This article aimed to study the effect of different concentrations of nano zinc oxide particles on the color change of MDX4–4210 facial silicone elastomer after artificial aging. Materials and Methods Silicone specimens (N = 150) were fabricated by incorporating intrinsic pigments and divided into three groups—white, yellow, and red, each group consisting of 50 specimens (n = 50). In each color, specimens were subdivided into five subgroups according to the quantity of zinc oxide nanoparticles (0, 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
1
8
0
1
Order By: Relevance
“…147 The previous research exhibited that incorporation of ZnO NPs at 2.0 to 2.5% by weight into silicone could improve the mechanical properties, including hardness, tensile and strength. 153 Popović synthesized a new composite material containing PMMA and ZnO NPs to identify its properties and behavior of modied PMMA. The ZnO NPs in the matrix of PMMA led to an increase of density owing to the reduced presence of residual monomers.…”
Section: Prosthodonticsmentioning
confidence: 99%
See 3 more Smart Citations
“…147 The previous research exhibited that incorporation of ZnO NPs at 2.0 to 2.5% by weight into silicone could improve the mechanical properties, including hardness, tensile and strength. 153 Popović synthesized a new composite material containing PMMA and ZnO NPs to identify its properties and behavior of modied PMMA. The ZnO NPs in the matrix of PMMA led to an increase of density owing to the reduced presence of residual monomers.…”
Section: Prosthodonticsmentioning
confidence: 99%
“…150 Charoenkijkajorn and Sanohkan indicated that addition of 0.5 to 2.0% of ZnO NPs remarkable decreased the color change of the silicone elastomer, and addition of 1.5% of ZnO NPs could improve the color stability of silicone prosthesis. 153 Moreover, Cierech et al investigated the nal ZnO NPs concentration on cytotoxicity and ZnO NPs released from PMMA-ZnO nanocomposites and the ZnO NPs layer produced on pure PMMA before being used as an alternative material for denture bases. 81 Summary of studies examining use of ZnO NPs in prosthodontics applications are shown in Table 6.…”
Section: Prosthodonticsmentioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7]9 The degradation of the physical and mechanical properties of a silicone prosthesis is related to its exposure to ultraviolet rays, polluted air, and humidity, as well as its inadequate cleaning and daily handling. 2,5,6,9 The literature reports that the replacement of a silicone prosthesis occurs from 3 to 12 months after its manufacture due to its degradation. 2,3,6 Sorption and solubility of a material are clinically important characteristics.…”
Section: Introductionmentioning
confidence: 99%